The Differences and Perspectives Between Elderly Individuals and Their Surrogates Regarding End-of-Life Care: A Mixed Methods Study. (September 2022) - Ke, Li-Shan; Hu, Wen-Yu; Dai, Yu-Tzu; Chen, Ching-Yu
Background: Family members often take the place of decision-making for elderly individuals. Previous studies showed that family members could not predict elderly individuals' thoughts about end-of-life care.Objectives: The aims are to understand the differences and perspectives between elderly individuals and surrogates regarding end-of-life care.Design: A mixed methods study comprising a cross-sectional survey and field notes analysis.Setting: Two geriatric wards in a veterans hospital located in northern Taiwan.Subjects: Fifty-five pairs of elderly individuals and their surrogates.Measurements: Life support preferences questionnaire and field notes.Results: The quantitative data showed that the elderly individuals and their surrogates had proper consistency in cardiopulmonary resuscitation and surgery. However, their consistency was poor in antibiotics and nasogastric tube feeding. Four themes were identified in qualitative data: recognizing old age, struggling with hope and peace, worries and concerns, and control of life. Recognizing old age for both elderly individuals and their surrogates was critical. Elderly individuals and their surrogates may seek a ray of hope among aggressive treatments and struggle with hope and peace. A lot of worries and concerns were mentioned, including contextual concerns. Elderly individuals need to depend on their ability to control their life.Conclusions: The study highlights elderly individuals' and their surrogates' considerations for antibiotics and nasogastric tube feeding. Furthermore, elderly individuals expressed that it is different for making decisions for themselves or others; thus, future studies can further explore whether elderly individuals allow their surrogates leeway from their wishes.